2020
DOI: 10.1590/1981-22562020023.200023
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de diagnóstico e tipos de câncer em idosos: dados da Pesquisa Nacional de Saúde 2013

Abstract: Resumo Objetivo: Estimar a prevalência de diagnóstico médico de câncer em idosos, descrever os tipos de câncer, as limitações em atividades cotidianas, autopercepção da saúde e a relação com doenças/condições crônicas. Métodos: Estudo transversal de base populacional com dados de idosos (n=11.177) que participaram da Pesquisa Nacional de Saúde (PNS/2013). Estimaram-se as prevalências e os respectivos intervalos de confiança de 95%. Resultados: A média de idade foi de 69,8 anos (IC95%:69,5-70,1) e 56,4% (IC95%:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
2
6
0
6
Order By: Relevance
“…The occurrence of neoplasms decreased in follow-up compared with baseline, suggesting a higher probability of death for part of the cohort that presented chronic disease. In a study using data from the 2013 PNS, the prevalence of cancer diagnosis was identified in 5.6% of older adults, and was higher in men (7.1%) than in women (4.7%; p<0.001), 34 similar to this study, which showed a higher occurrence of neoplasms in older men. Older adults with cancer who participated in the 2013 PNS showed an even higher prevalence of arterial hypertension, heart diseases, depression and chronic respiratory diseases, which reflects the association between CNCDs (multimorbidity), their clinical implications and in oncogeriatric care.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The occurrence of neoplasms decreased in follow-up compared with baseline, suggesting a higher probability of death for part of the cohort that presented chronic disease. In a study using data from the 2013 PNS, the prevalence of cancer diagnosis was identified in 5.6% of older adults, and was higher in men (7.1%) than in women (4.7%; p<0.001), 34 similar to this study, which showed a higher occurrence of neoplasms in older men. Older adults with cancer who participated in the 2013 PNS showed an even higher prevalence of arterial hypertension, heart diseases, depression and chronic respiratory diseases, which reflects the association between CNCDs (multimorbidity), their clinical implications and in oncogeriatric care.…”
Section: Discussionsupporting
confidence: 87%
“…Older adults with cancer who participated in the 2013 PNS showed an even higher prevalence of arterial hypertension, heart diseases, depression and chronic respiratory diseases, which reflects the association between CNCDs (multimorbidity), their clinical implications and in oncogeriatric care. 34 Several measures have been implemented in recent years to control CNCDs in Brazil, with free access to drug treatment forming an essential strategy for health policies. Matta et al 35 identified the pharmacy of the Unified Health System as the main source of obtaining medicines in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…A proporção de ocorrência de neoplasias reduziuse no seguimento em comparação com a linha de base, sugerindo maior probabilidade de falecimento para parte da coorte que apresentou a doença crônica. Em estudo com dados da PNS 2013, a prevalência do diagnóstico de câncer foi identificada em 5,6% dos idosos, sendo maior nos homens (7,1%) do que nas mulheres (4,7%; p<0,001) 34 , semelhante ao presente estudo que evidenciou maior ocorrência de neoplasias em idosos do sexo masculino. Idosos com câncer que participaram da PNS 2013 apresentaram ainda maiores prevalências de hipertensão arterial, doenças do coração, depressão e doenças respiratórias crônicas, o que reflete a associação entre as DCNT (multimorbidade), suas implicações clínicas e no cuidado oncogeriátrico 34 .…”
Section: Discussionunclassified
“…Nas mulheres, as neoplasias malignas da mama representaram 12% e de traqueia, brônquios e pulmões corresponderam a 11%. Estimativas da incidência de câncer no Brasil, realizada pelo Instituto Nacional do Câncer (INCA), apontam para cada ano do triênio 2020-2022, um total de 625 mil casos novos, com maior incidência para o câncer de pele não melanoma (177 mil), seguido pelos cânceres de mama e próstata (66 mil cada) (Francisco et al, 2020).…”
Section: Neoplasias E Seus Impactos Na Saúde Da Pessoa Idosaunclassified